Beryllium detection in the very fast nova ASASSN-16kt (V407 Lupi). Issue 2 (21st February 2018) - Izzo, L; Molaro, P; Bonifacio, P; Della Valle, M; Cano, Z; de Ugarte Postigo, A; Prieto, J L; Thöne, C; Vanzi, L; Zapata, A; Fernandez, D
ABSTRACT: We present high-resolution spectroscopic observations of the fast nova ASASSN-16kt (V407 Lup). A close inspection of spectra obtained at early stages has revealed the presence of low-ionization lines, and among the others we have identified the presence of the ionized 7 Be doublet in a region relatively free from possible contaminants. After studying their intensities, we have inferred that ASASSN-16kt has produced (5.9–7.7)× 10 −9  M⊙ of 7 Be. The identification of bright Ne lines may suggest that the nova progenitor is a massive (1.2 M⊙ ) oxygen–neon white dwarf. The high outburst frequency of oxygen–neon novae implies that they likely produce an amount of Be similar, if not larger, to that produced by carbon–oxygen novae, then confirming that classical novae are among the main factories of lithium in the Galaxy.